Experimental dataset to develop a parametric model based of DC geared motor in feeder machine - Azlan. W. M.; Salleh S. M.; Mahzan S; Sadikin A; Ahmad S (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents the application of a System Identification based on Particle Swarm Optimization (PSO) technique to develop parametric model of experimental dataset of DC Geared motor in feeder machine. The experimental was conducted to measure the input (voltage) and output (speed) data. The actual data is used to be optimized using PSO algorithm. The parameter emphasized is Time, Man Square Error (MSE) and Average Time. One of the best model has been chosen based on the optimum parameters.